2017
DOI: 10.1177/0972150917693334
|View full text |Cite
|
Sign up to set email alerts
|

Study of Early Recruitment Activities and Employer Brand Knowledge and Its Effect on Organization Attractiveness and Firm Performance

Abstract: This article explores the various dimensions of early recruitment activities (ERAs) such as publicity, sponsorship, word of mouth and advertisement, and its impact on employer brand knowledge (EBK) such as employer familiarity, employer image or job association and employer reputation. It further explores the impact of ERAs and EBK on organization attractiveness (OA) and firm performance (FP). The study shows that advertisement, publicity and word of mouth of ERAs impact all aspects of EBK such as employer fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 68 publications
1
22
0
Order By: Relevance
“…Since Ambler and Barrow (1996) originally coined the term employer branding, research on this topic has progressed in several regards (see the reviews of Theurer et al 2018;Lievens and Slaughter 2016). Besides conceptual articles (e.g., Backhaus and Tikoo 2004;Edwards 2010;Martin et al 2011), a steady stream of predominantly quantitative empirical research has been conducted in the field of employer branding, particularly in terms of analyzing the effects of employer brand activities and material on potential applicants' perceptions of employer images and attractiveness (e.g., Onken-Menke et al 2018;Kashive and Khanna 2017;Baum and Kabst 2014). Additionally, employer branding studies have investigated current and potential employees' perceptions of attributes of organizations as employers (e.g., Kumari and Saini 2018;Edwards and Edwards 2013;Van Hoye et al 2013;Lievens 2007;Lievens and Highhouse 2003).…”
Section: Proposing a Subjective And Process-oriented Perspective On Employer Brandingmentioning
confidence: 99%
“…Since Ambler and Barrow (1996) originally coined the term employer branding, research on this topic has progressed in several regards (see the reviews of Theurer et al 2018;Lievens and Slaughter 2016). Besides conceptual articles (e.g., Backhaus and Tikoo 2004;Edwards 2010;Martin et al 2011), a steady stream of predominantly quantitative empirical research has been conducted in the field of employer branding, particularly in terms of analyzing the effects of employer brand activities and material on potential applicants' perceptions of employer images and attractiveness (e.g., Onken-Menke et al 2018;Kashive and Khanna 2017;Baum and Kabst 2014). Additionally, employer branding studies have investigated current and potential employees' perceptions of attributes of organizations as employers (e.g., Kumari and Saini 2018;Edwards and Edwards 2013;Van Hoye et al 2013;Lievens 2007;Lievens and Highhouse 2003).…”
Section: Proposing a Subjective And Process-oriented Perspective On Employer Brandingmentioning
confidence: 99%
“…As for signals structuring the organization image, companies should use effective employer branding strategies in order to generate positive images "as a unique and preferable employer" (Lievens et al, 2007) . Companies must consider the context of the information shared to the stakeholders, the sources of information and the creditability of each source in order to be attractive and to build a good image as an employer (Kashive and Khanna, 2017;Slaughter et al, 2014;Liu et al, 2016;Kashive;Khanna, 2017). The job seeker is motivated to look for the available information about the employer or the job vacancy in order to form accurate perceptions regarding the employer; whether it is a good place to work at or not.…”
Section: 32mentioning
confidence: 99%
“…Although researchers agreed that the images of the employer and the corporate are important factors affecting organizational attractiveness (OA), most studies examine the effect of both of them separately. For example, studies tackled the relation between corporate image and employer attractiveness (Belt and Paolillo, 1982;Rynes, 1989;Gatewood et al, 1993) or the relation between employer image and employer attractiveness (Myrden and Kelloway, 2015;Van Hoye and Saks, 2011;Kashive and Khanna, 2017). Notwithstanding these first findings, reviewing the literature reveals a gap in studying the impact of corporate and employer images on the same model.…”
Section: Introductionmentioning
confidence: 99%
“…Past studies have found that traditional public media impact all aspects of employer brands, including familiarity and reputation (e.g., U.S. Fortune 500 companies), and familiarity and reputation drive organizational attractiveness for both internal employees and external candidates, because the ranking list may signal that companies have a higher degree of familiarity and better reputation, which can make employees (and potential employees) feel pride for being (or having ever been) a part of these companies [23]. Therefore, how much the degree of familiarity and reputation ranked by the public on social media influence employer ratings ranked by internal employees would be a third research question in this project.…”
Section: Introductionmentioning
confidence: 99%